Determinação multirresíduo de agrotóxicos em abelha e pólen apícola empregando método QuEChERS modificado e LC-MS/MS - Saibt, Nathália (2017)
The use of pesticides contributes to increase the production, but there is a growing concern with its adverse effects in the environment. The decline of bee population and the contamination of apicultural products by pesticide residues has been widely discussed. Thus, this work had as main objective to develop and validate a method for determination of pesticide residues in bee and bee pollen samples, using liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) for detection of 81 compounds from different classes, such as insecticides and fungicides. The method involves a homogenization step of the bees and bee pollen samples using aqueous solution of trichloroacetic acid followed by acetonitrile extraction, partition and clean-up with magnesium sulfate, PSA, C18 and GCB. The method was validated evaluating the parameters linearity, accuracy, precision, limit of detection (LOD), limit of quantification (LOQ) and matrix effect. The determination of pesticide residues in bee and apicultural products samples by the proposed method is rapid and simple, and the method showed to be effective for pesticide multiresidue analysis. The validation results, evaluated by recovery assays at 4 spiked levels, were satisfactory, with accuracy from 70 to 120%, RSD ˂20%, linearity from 5 to 200 μg kg-1, determination coefficient (r2) >0.99, LOD of 1.5 to 15 μg kg-1 and LOQ of 5 to 50 μg kg-1. The proposed method was applied to bee pollen samples and bees samples, obtained from different regions of the state of Rio Grande do Sul, Brazil, and all of them presented residues pesticides, however below the to the maximum residue limit established by the European legislation.